A new time‐domain corner diffraction coefficient for metallic and dielectric objects for UWB signals. Issue 7 (July 2015) - Bansal, Bajrang; Soni, Sanjay
ABSTRACT In this article, a new time‐domain (TD) corner diffraction coefficient is proposed for diffraction of ultrawide band signals by objects like metallic and dielectric three‐dimensional wedge and building. The proposed TD solution has been validated with the inverse fast Fourier transform of the corresponding frequency‐domain (FD) solution where the exact match confirms the accuracy of the proposed solution. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1760–1765, 2015